Classification of Agricultural Pests Using Statistical and Color Feature Extraction and Support Vector Machine - Datta, Aparajita; Dey, Abhishek; Dey, Kashi Nath (International Journal of Computer Sciences and Engineering, 2025)
Beetles and bugs are most common harmful pests that affect plants easily and can damage entire plant. Most of the beetles and bugs bruise the front surface of leaves to lay eggs so and some of the bugs feed on the extract of leaves. So, the leaves get damaged often and it is essential to detect pest affected leaves as early as possible to take further precautions. In this paper, an automated approach based on digital image processing and machine learning is used to classify three vulnerable pests - blue mint beetle, white mealy bug and red lily beetle from affected leaf images. Image pre-processing methods like noise removal and contrast enhancement followed by color space transformation and k-means clustering is used to segment affected parts of leaves, after that both texture and color features are extracted from segmented leaves and based on extracted features support vector machine classification method is used to classify the pests.